2019
DOI: 10.1093/biosci/biz027
|View full text |Cite
|
Sign up to set email alerts
|

The Invisible Flood: The Chemistry, Ecology, and Social Implications of Coastal Saltwater Intrusion

Abstract: Saltwater intrusion is the leading edge of sea-level rise, preceding tidal inundation, but leaving its salty signature far inland. With climate change, saltwater is shifting landward into regions that previously have not experienced or adapted to salinity, leading to novel transitions in biogeochemistry, ecology, and human land uses. We explore these changes and their implications for climate adaptation in coastal ecosystems. Biogeochemical changes, including increases in ionic strength, sulfidation, and alkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(135 citation statements)
references
References 69 publications
0
111
1
2
Order By: Relevance
“…With sea-level rise, saltwater is shifting landward into regions that previously have not experienced or adapted to salinity (Tully et al 2019). Surface and near-surface drinking water in low-lying coastal areas, such as the mega-deltas in Vietnam and Bangladesh−India, are most vulnerable to saltwater intrusion, where more than 25 million people are at risk of drinking 'saline' water (Hoque et al 2016).…”
Section: Saltwater Intrusionmentioning
confidence: 99%
“…With sea-level rise, saltwater is shifting landward into regions that previously have not experienced or adapted to salinity (Tully et al 2019). Surface and near-surface drinking water in low-lying coastal areas, such as the mega-deltas in Vietnam and Bangladesh−India, are most vulnerable to saltwater intrusion, where more than 25 million people are at risk of drinking 'saline' water (Hoque et al 2016).…”
Section: Saltwater Intrusionmentioning
confidence: 99%
“…In low‐lying coastal areas of the Chesapeake Bay, there is growing concern that climate‐change‐induced sea level rise could render agricultural soils in these regions more vulnerable to P loss due to saltwater intrusion. While the risk of enhanced P mobilization with increased salinity is well understood (Jordan et al, 2008; Hartzell and Jordan, 2012; Upreti et al, 2015), the potential for saltwater intrusion to enhance legacy P losses from agriculture is receiving increasing attention (Tully et al, 2019a, b). Indeed, a recent study on Maryland's Lower Eastern Shore found increasing soil P concentrations along saltwater intrusion gradients in several farm fields (Tully et al, 2019b), while a laboratory study using coastal wetland soils from Florida showed enhanced P losses with increased salinization (Steinmuller and Chambers, 2018).…”
Section: Climate Changementioning
confidence: 99%
“…Sea-level rise has the potential to affect coastal aquaculture operations through loss of culture area (Hargreaves 2014), greater and more distant salt intrusion into coastal groundwater (Ahmed 2013, Nguyen et al 2014, Smajgl et al 2015, Tully et al 2019, and, in some areas, the augmentation of seasonal or episodic flooding via storm surges (Wassmann et al 2004, Rhein et al 2013. Global mean sea level rose 1.2 ± 0.2 mm yr −1 between 1901 and 1990, with this rate increasing to 3.0 ± 0.7 mm yr −1 between 1993 and 2010 (Hay et al 2015).…”
Section: Sea-level Risementioning
confidence: 99%